A STUDY ON ANALYZING CAUSES OF RESTRUCTURING OF PUBLIC SECTOR BANKS (Journal of Informatics Education and Research, 2024)
Banking institutions must regularly reevaluate and realign to be competitive and relevant as economies change and change dramatically. Being key actors in economies worldwide, public sector banks go through restructuring to respond to new challenges, technology improvements, and changing consumer expectations. It is essential for the stability and effectiveness of the banking sector to comprehend the reasons behind reorganisation. The purpose of this research is to evaluate the causes of the restructuring of public sector banks.  The technique used in this study is non-parametric Wilcoxon one sample signed rank test. The outcome of the study indicated that non-performing assets, Inadequate capital adequacy, Poor financial performance, Outdated technology infrastructure, Global financial crises, Non-compliance with regulatory norms, Ineffective management practices and Lack of customer satisfaction were seen to be high causes. In contrast, Privatization and Political interference were low causes of restructuring public sector banks.